The Health Gains, Financial Risk Protection Benefits, and Distributional Impact of Increased Tobacco Taxes in Armenia - Postolovska, Iryna (Taylor and Francis, 2018)
The majority of Armenian adult males smoke, yet tobacco taxes in Armenia are among the lowest in Europe and Central Asia. Increasing taxes on tobacco is one of the most cost-effective public health interventions, but many opponents often cite regressivity as an argument against tobacco taxation. We use a mixed-methods approach to study the potential regressivity of tobacco taxation and the extent to which the regressivity argument hindered increases in tobacco taxation in Armenia. First, we pursued an extended cost-effectiveness analysis (ECEA) to assess the health, financial, and distributional consequences (by consumption quintile) of increases in the excise tax on cigarettes in Armenia. We simulated a hypothetical price hike leading to a tax rate of about 75% of the retail price of cigarettes, which would be fully passed on to consumers. Second, we conducted a series of stakeholder interviews to examine the importance of the regressivity argument and identify the factors that allowed tobacco tax increases to be adopted as public policy in Armenia. We show that increased excise taxes would bring large health and financial benefits to Armenian households. Half of tobacco-related premature deaths and 27% of associated poverty cases averted would be concentrated among the bottom 40% of the population. Though regressivity was raised as a concern at the initial stages of the policy adoption process, our qualitative stakeholder analysis indicates that the recent accession to the Eurasian Economic Union and the fiscal constraints faced by the government created a window of opportunity for tobacco taxation to be placed on the policy agenda and adopted as government policy, and the ECEA findings were an important input into the process.